DIFFERENCE IN HAULING TIME OF STATIONARY LIFT NET ON THE CATCH FISH IN THE PELAPIS VILLAGE OF KARIMATA ISLANDS DISTRICT KAYONG UTARA - Erni, Supia (Jurnal Sains Pertanian Equator, 2019)
The stationary lift net is a fishing device consisting of a rectangular nibung bamboo arrangement which is fixed with fixed construction so that it stands firmly on the water and in the middle of the building a net is installed which serves as a tool to catch fish, operated by being lifted. Hauling time is the time the net is drawn. This study aims to determine the differences in the hauling time of the stationary lift net with the catch and determine the optimal hauling time on the stationary lift net. This research conducted on 12 August - 2 September 2018 in the Pelapis Village of Karimata Islands District, Kayong Utara. The research method used a completely randomized design with one factor, namely the hauling time stepping device. The time of hauling (W) way divided into three levels, namely 17.00-20.00 WIB (w1), 20.00-00.00 WIB (w2) and 00.00-04.00 WIB (w3). Sampling was condycted done by using 9 units of stationary lift net as replications. by test has 4 weeks of data collection and done once a week. Observation variables include: the weight of anchovy and the weight of tamban fish. The results showed that there were no variables that significantly affected the catch of the stationary lift net. Keywords : Stationary Lift net Catch Fish, The water of the Pelapis Village, Hauling time.